From Gut to Lung: The Role of Bile Acids in Rheumatoid Arthritis-Associated Interstitial Lung Disease (RA-ILD) - Shi YJ; Lin S; Shi YC; Xie J (Journal of Inflammation Research)
Yu-jia Shi,1 Shu Lin,2,3 Yan-Chuan Shi,3,4 Jianmin Xie1 1Department of Rheumatology and Immunology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2Centre of Neurological and Metabolic Research, The Second Affiliated Hospital of Fujian Medical University, Quanzhou, Fujian, People’s Republic of China; 3Neuroendocrinology Group, Garvan Institute of Medical Research, Darlinghurst, NSW, 2010, Australia; 4St Vincent’s Clinical School, Faculty of Medicine, The University of New South Wales, Sydney, NSW, AustraliaCorrespondence: Jianmin Xie, Department of Rheumatology and Immunology, The Second Affiliated Hospital of Nanjing Medical University, No. 121 Jiangjiayuan, Nanjing, Jiangsu, 210000, People’s Republic of China, Email xiejmdoc@163.com Yan-Chuan Shi, Neuroendocrinology Group, Garvan Institute of Medical Research, 384 Victoria Street, Darlinghurst, NSW, 2010, Australia, Email y.shi@garvan.org.auAbstract: Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is a serious complication of rheumatoid arthritis (RA) that significantly increases both morbidity and mortality. Although advances have been made in elucidating the pathogenesis of RA-ILD, the specific roles of bile acids remain underexplored. Bile acids are known to modulate immune responses, potentially influencing the inflammatory processes central to RA-ILD; however, their exact mechanisms and therapeutic utility remain unclear. This review aims to elucidate the diverse functions of bile acids, highlighting their potential as both biomarkers of disease activity and as novel therapeutic agents to mitigate pulmonary inflammation and fibrosis. By exploring the gut–lung axis and the interactions between bile acid metabolism and immune responses, the review seeks to identify new avenues for RA-ILD treatment. It also discusses the emerging role of bile acid-derived exosomes in RA and RA-ILD, emphasizing their promise as vehicles for modulating inflammation. This review highlights the significance of current findings and the need for further studies to validate bile acids and their derivatives as reliable markers and effective therapies. By reviewing available research and identifying critical gaps for future research, this review aims to enhance our understanding of RA-ILD and to support the development of targeted interventions that could markedly improve patient outcomes.Keywords: rheumatoid arthritis, interstitial lung disease, bile acids, pulmonary fibrosis, RA-ILD